Pro-inflammatory Cytokines Drive Deregulation of Potassium Channel Expression in Primary Synovial Fibroblasts - Haidar, Omar; O’Neill, Nathanael; Staunton, Caroline A.; Bavan, Selvan; O’Brien, Fiona; Zouggari, Sarah; Sharif, Umar; Mobasheri, Ali; Kumagai, Kosuke; Barrett-Jolley, Richard (Frontiers in Physiology, 2020)
The synovium secretes synovial fluid, but is also richly innervated with nociceptors and acts as a gateway between avascular joint tissues and the circulatory system. Resident fibroblast-like synoviocytes’ (FLS) calcium-activated potassium channels (KCa) change in activity in arthritis models and this correlates with FLS activation. Objective: To investigate this activation in an in vitro model of inflammatory arthritis; 72hr treatment with cytokines TNF and IL1. Methods: FLS cells were isolated from rat synovial membranes. We analysed global changes in FLS mRNA by RNA-sequencing and then focused on FLS ion channels genes and corresponding FLS electrophysiological phenotype, finally modelling data with Ingenuity Pathway Analysis (IPA) and MATLAB. Results: IPA showed significant activation of inflammatory, osteoarthritic and calcium signalling canonical pathways by cytokines, and we identified 200 channel gene transcripts. The large KCa (BK) channel consists of the pore forming Kcnma1 together with -subunits. Following cytokine treatment, a significant increase in Kcnma1 RNA abundance was detected by qPCR and changes in several ion channels were detected by RNA-sequencing, including a loss of BK channel -subunit expression Kcnmb1/2 and increase in Kcnmb3. In electrophysiological experiments, there was a decrease in over-all current density at 20mV without change in chord conductance at this potential. Conclusion: TNF and IL1 treatment of FLS in vitro recapitulated several common features of inflammatory arthritis at the transcriptomic level, including increase in Kcnma1 and Kcnmb3 gene expression.